Reduced store‐operated Ca2+ entry impairs mesenteric artery function in response to high external glucose in type 2 diabetic ZDF rats. (30th March 2020) - Schach, Christian; Wester, Michael; Leibl, Florian; Redel, Andreas; Gruber, Michael; Maier, Lars S.; Endemann, Dierk; Wagner, Stefan
Abstract: Diabetes is a major risk factor for cardiovascular disease, affecting both endothelial and smooth muscle cells. Store‐operated Ca 2+ channels (SOCCs) have been implicated in many diabetic complications. Vascular dysfunction is common in patients with diabetes, but the role of SOCCs in diabetic vasculopathy is still unclear. Our research aimed to investigate the effects of high glucose (HG) on store‐operated Ca 2+ entry (SOCE) in small arteries. Small mesenteric arteries from type 2 diabetic Zucker fatty rats (ZDF) versus their non‐diabetic controls (Zucker lean, ZL) were examined in a pressurized myograph. Vascular smooth muscle cells (VSMC) were isolated and intracellular Ca 2+ was measured (Fura 2‐AM). A specific protocol to deplete intracellular Ca 2+ stores and thereby open SOCCs, as well as pharmacological SOCE inhibitors (SKF‐96365, BTP‐2), were used to artificially activate and inhibit SOCE, respectively. High glucose (40 mmol/L) relaxed arteries in a SKF‐sensitive manner. Diabetic arteries exhibited reduced HG‐induced relaxation, as well as reduced contraction after Ca 2+ replenishment. Further, the rise in intracellular Ca 2+ on account of SOCE is diminished in diabetic versus non‐diabetic VSMCs and was insensitive to HG in diabetic VSMCs. The expression of SOCC proteins was measured, detecting a downregulation of Orai1 in diabetes. In conclusion, diabetes leads to a reduction of SOCE and SOCE‐induced contraction, which is unresponsive to HG‐mediated inhibition. The reduced expression of Orai1 in diabetic arteries could account for the observed reduction in SOCE.